(untitled) (European Journal of Marketing and Economics, 2025)
Since the late 1970s, China’s economy has altered in one of the most profound ways in modern economic history. After decades of state-led planning and relative isolation, China has become the world’s second-largest economy, the biggest exporter, and a significant actor in global economic governance. This paper looks at what scholars have said about China’s economy over the years. It talks about the history of reforms, what produced rapid growth (including urbanization, investment, and innovation), and the challenges that come with debt, changing demographics, and inequality. It also talks about how China’s trade, banking, and geopolitical influence affect the world economy and what China should do to be strong in the future. The assessment reveals the inconsistencies between state-driven development and market liberalization, economic growth and inequality, as well as globalization and domestic security. It says that China’s manner of growing is a one-of-a-kind mix that is always evolving. However, it also has difficulties that are getting worse and will have an impact on the future of both China and the world.